Denitrification occurring on suspended sediment in a large, shallow, subtropical lake (Poyang Lake, China). (December 2016) - Yao, Xiaolong; Zhang, Lu; Zhang, Yunlin; Xu, Huixian; Jiang, Xingyu
Abstract: Many lakes and rivers are enriched with high levels of suspended sediments (SPS). Denitrification occurring on suspended sediments (DSS) may play an important role in nitrogen removal in water columns with high SPS concentrations. Poyang Lake, with dramatic hydrologic variations, has high spatial and seasonal variation of SPS, and we hypothesized that DSS and nitrogen removal in this lake would vary similarly. DSS in Poyang Lake was determined by the traditional acetylene-inhibition method combined with a batch mode assay. Laboratory simulation experiments were also conducted to examine the factors controlling denitrification occurring on SPS. Seasonally, DSS rates at 15 sampling sites in Poyang Lake were 0.63 ± 0.24, 0.29 ± 0.17, 0.25 ± 0.18, and 0.52 ± 0.37 μmol N·L −1 ·d −1, respectively in spring, summer, autumn, and winter. Spatially, average DSS rates were higher in the northern lake area, which is connected to the Yangtze River, than in the upstream and central lake area. Lowest DSS rates occurred in semi-closed bay and dish lakes. Spatial and seasonal variations of DSS rates were affected by a combination of factors, in which nitrate concentrations, SPS composition, and concentrations of organic-SPS were the most important. These influencing factors were seasonally dependent, with nitrate concentrations having stronger effects on DSS during wet seasons than dry seasons. Results from a multiple stepwise regression model also demonstrated that DSS tended to occur on fine particles (e.g., clay particles, <4 μm). Evaluation of annual nitrogen loss by DSS was estimated according to the seasonal water budget and DSS rates in Poyang Lake. The total nitrogen loss by DSS was estimated to be 10800 ± 6090 t, which accounted for 2.8–9.9% of the nitrogen input, and this proportion was comparable to nitrogen removal by sediment denitrification. This result confirms that DSS was an important nitrogen sink in this large, turbid lake. Graphical abstract: Highlights: Nitrogen loss by denitrification occurring on suspended sediment (DSS) accounted for 2.8–9.9 % of the nitrogen inputs in Poyang Lake. Nitrogen loss by DSS was comparable to bottom sediment in Poyang Lake. DSS was controlled by nitrate concentrations, SPS compositions and concentrations of organic-SPS.